Efektivitas Parem Kunyit Pada Payudara Ibu Menyusui Terhadap Kelancaran Produksi ASI Di PMB L Kota Tangerang Tahun 2022: The Effectiveness of Parem Turmeric on the Breasts of Breastfeeding Mothers for Smooth Milk Production at PMB L Tangerang City in 2022 - Hernawati, Lenti (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Exclusive breastfeeding that is still low can cause babies. Puskesmas Sangiang Tangerang City exclusive breastfeeding coverage in 2020 was 71,6%, meanwhile, in 2021 it decreased to 64,6%. One way to increase breast milk production is by using traditional medicine by giving turmeric parem while doing breast care with the ingredients in it, including rice, kencur, fenugreek seeds, moringa leaves, and turmeric. Knowing the effectiveness of turmeric parem on the breasts of nursing mothers on the smooth production of breast milk in PMB L Tangerang City in 2022.  Methods: This research is a quasi-experiment with a one-group pretest-posttest design method. The sample in this study were postpartum mothers who gave birth at PMB L, Tangerang City, on October 1-4 2022, with as many as 30 respondents using a total sampling technique.  Result: Data were analyzed using the Wilcoxon test with a 95% confidence level (α = 0,05). The results of the univariate analysis showed that breast milk production before being given turmeric parem to breastfeeding mothers and after being given turmeric parem was mostly not smooth as much as 63,3%. The results of bivariate analysis obtained p-value = 0,000 <0,005.  Discussion: There is the effectiveness of turmeric parem on the breasts of nursing mothers on the smooth production of breast milk. Breastfeeding mothers are expected to know and apply the breast care process using turmeric parem to increase breast milk production.